Yield and yield components of superior cocoa (Theobroma cocoa L.) clones rejuvenated by ring budding technique - Resti Utari Wahyudi; Eka Tarwaca Susila Putra; Didik Indradewa (Jurnal Ilmu Pertanian, 2023)
The ring budding technique gave a higher suitability for rejuvenation of cocoa plants compared to side cleft grafting it can be combined with the use of superior clones for optimal production. However, information related to this is still limited. The research aimed to determine the effects of ring budding technique on yield components and yields of three types of superior cocoa clones. The experiment was arranged in a Nested Design. The first factor is the type of vegetative propagation technique, consisting of side cleft grafting and ring budding. The second factor was clones, which consisted of clones KKM 22, RCC 70 and RCC 71. Clones were nested in vegetative propagation. The research was conducted from September 2020 to January 2021 at the Pagilaran Company. Observations were made on several yield component variables. The data were analyzed using Analysis of Variance (ANOVA) and continued with the Least Significant Difference Test (LSD) at the 5%. The results showed that the number of pods and the weight of beans per cocoa stand were significantly higher in the ring budding technique than the side cleft grafting. This condition caused the dry bean weight per hectare much higher as well. The three cacao clones, which were rejuvenated by ring budding, gave a good response and high yields. Meanwhile, only KKM 2 gave good response and high yield after treated with side cleft grafting technique, while  RCC 70 and RCC 71 clones gave low yields. The KKM 22 clone is the best option in terms of rehabilitation with ring budding and side cleft grafting.